Environmental Factors in Primary Biliary Cirrhosis - Juran, Brian D.; Lazaridis, Konstantinos N. (Seminars in Liver Disease, 2014)
The etiology of the autoimmune liver disease primary biliary cirrhosis (PBC) remains largely unresolved, owing in large part to the complexity of interaction between environmental and genetic contributors underlying disease development. Observations of disease clustering, differences in geographical prevalence, and seasonality of diagnosis rates suggest the environmental component to PBC is strong, and epidemiological studies have consistently found cigarette smoking and history of urinary tract infection to be associated with PBC. Current evidence implicates molecular mimicry as a primary mechanism driving loss of tolerance and subsequent autoimmunity in PBC, yet other environmentally influenced disease processes are likely to be involved in pathogenesis. In this review, the authors provide an overview of current findings and touch on potential mechanisms behind the environmental component of PBC.
Keywords: autoimmunity; environment; primary biliary cirrhosis